Lentivirus vector in gene therapy of β-thalassemia - LIU Yize, CHAN Ying, ZHU Baosheng (Jichu yixue yu linchuang, 2023)
β-thalassemia is a common monogenic inherited blood disorder caused by mutations of β-globin gene which results to synthesis obstacles or abnormal structure of β-globin. Gene therapy mediated by lentiviral vector(LVV) is divided into gene-integration strategies using LVV to add fully functional β-hemoglobin(HBB) genes to chromosomes and gene-editing strategies using LVV to deliver specific ribozymes to hematopoietic stem cells for in situ repair of HBB genes. Improving viral titration and transduction efficiency, reducing target loss and advancing clinical trials are the main targets of these two strategies.